Dual antiplatelet therapy may increase the risk of non-intracranial haemorrhage in patients with minor strokes: a subgroup analysis of the CHANCE trial. Issue 2 (16th June 2016) - Wang, David; Gui, Li; Dong, Yi; Li, Hao; Li, Shujuan; Zheng, Huaguang; Wang, Anxin; Meng, Xia; Liu, Li-Ping; Wang, Yi-Long; Wang, Guangyao; Jing, Jing; et al.
Abstract : Aim: The aim of this study was to explore the difference between haemorrhagic events among those patients on either aspirin or aspirin plus clopidogrel who were enrolled in the Clopidogrel in High-Risk Patients with Acute Non-disabling Ischemic Cerebrovascular Events (CHANCE) trial. Methods: This was an ad hoc analysis of the CHANCE trial; data on all patients with any haemorrhagic event were reviewed and analysed. Cox proportional hazards regression was used to determine factors association with any bleeding. Results: In the CHANCE trial, there were a total of 101 (2%) haemorrhagic events reported from 50 different hospitals. The clopidogrel–aspirin group had 60 (2.3%) cases and the aspirin group had 41 (1.6%, p=0.09). Moderate or severe haemorrhagic events occurred in 7 patients (0.3%) in the clopidogrel–aspirin group and in 8 (0.3%) in the aspirin group (p=0.73). Of 36 (0.7%) cases of intracranial haemorrhages, 20 (0.4%) were in the clopidogrel–aspirin group and 16 (0.3%) in the aspirin group. Each group had 8 (0.3%) cases of symptomatic haemorrhagic strokes. Other common haemorrhagic events included 24 (0.5%) cases of skin bruises, 13 (0.3%) gastrointestinal haemorrhages, 9 (0.2%) gum haemorrhages and 8 (0.2%) intraocular haemorrhages. Conclusions: There was no overall significant difference in haemorrhagic events (p=0.29), especially in the rate of intracranial haemorrhages between the 2 treatment groups. However, patients enrolled with minor strokes had an increased risk of haemorrhagic events regardless of treatment group, not seen in patients with high-risk transient ischaemic attacks. Being elderly, of male gender and with a history of aspirin or proton pump inhibitor usage were associated with increased risk of haemorrhage. Patients with higher body mass index had lower risk of haemorrhagic events. Trial registration number: NCT00979589.